Masculinidades e experiências masculinas em Bernardo Guimarães Masculinities and masculine experiences in Bernardo Guimarães' literary work - Luciano Mendes de Faria Filho (Cadernos Pagu, 2010)
Neste trabalho identificamos e analisamos as diferentes facetas da masculinidade apresentadas na obra de um dos mais importantes literatos brasileiros do século XIX: o mineiro Bernardo Guimarães. Sem abandonar as representações de feminilidade, enfocamos como o autor, em suas diversas obras, constrói as relações de gênero e produz representações sobre homens e mulheres, dando especial relevo às experiências de masculinidade. Desse modo, pretendemos, também, contribuir para uma maior compreensão da forma como, no final do século XIX, a literatura teve uma participação na produção de representações e práticas de masculinidade (e de feminilidade) no Brasil. This article aims to identify and analyze different aspects of masculinity presented in the literature of Bernardo Guimarães, an important 19th century Brazilian writer from Minas Gerais. We shall focus how the author, in his literary work, constructs the gender relations and produces representations about men and women, specially the masculine experiences, without forgetting the feminine ones. We intend, in the same way, to contribute to a broader understanding of the participation of literature in the production of representations and practices of masculinity (and of femininity) in late nineteenth-century Brazil.